Duty, honor, country & life : a tribute to the American spirit - McRaven, William H. (William Harry), 1955- (Grand Central, 2026)
"In the tradition of Make Your Bed, The Hero Code and The Wisdom of the Bullfrog, Duty, Honor, Country and Life is an uplifting selection of curated speeches, letters, toasts, and original poems that capture the essence of who we are as Americans"-- Provided by publisher.